The Effect of Premium on Profit of Life Insurance Companies in Sharia Units of Pt Panin Dai-Ichi Life Indonesia - Ridwan Tabe (Tasharruf: Journal Economics and Business of Islam, 2019)
Abstract:This study discusses the effect of premiums on life insurance company profits in Sharia Unit of PT Panin Dai-Ichi Life Indonesia's. The main problem is the effect of premiums on profits of Life Insurance companies in Sharia Unit of PT Panin Dai-Ichi Life Indonesia from 2012-2016.The type of research method is quantitative. The population in this study is financial statements from PT Panin dai-Ichi Life Indonesia, while the sample is financial statements from 2012 - 2016. Data analysis techniques used in this study are normality test, hypothesis test, and T test using simple linear regression analysis.The results of this study concluded that the premium has an effect on profit where the value of T count - 4.366 <from the value of T table l2.101. While the significance is 0,000 smaller than 0.05 and for the value of F count is 19,067 > 4.41 F table. The significance of anova table 0.000 is smaller than 0.05, so Ho is rejected and Ha is accepted. It means that, there is a significant effect of premium on profit.Keywords: Premium, Profit, Life Insurance